Coronavirus disease 2019: Utilizing an ethical framework for rationing absolutely scarce health‐care resources in transplant allocation decisions. Issue 9 (26th April 2020) - Wall, Anji E.; Pruett, Timothy; Stock, Peter; Testa, Giuliano
Abstract : The novel coronavirus disease 2019 (COVID‐19) is impacting transplant programs around the world, and, as the center of the pandemic shifts to the United States, we have to prepare to make decisions about which patients to transplant during times of constrained resources. In this paper, we discuss how to transition from the traditional justice versus utility consideration in organ allocation to a more nuanced allocation scheme based on ethical values that drive decisions in times of absolute scarcity. We recognize that many decisions are made based on the practical limitations that transplant programs face, especially at the extremes. As programs make the transition from a standard approach to a resource‐constrained approach to transplantation, we utilize a framework for ethical decisions in settings of absolutely scarce resources to help guide programs in deciding which patients to transplant, which donors to accept, how to minimize risk, and how to ensure the best utilization of transplant team members. Abstract : The authors discuss how transplant centers can apply an ethical values framework to decision‐making regarding who to transplant and which organs to accept when faced with resource constraints due to the coronavirus pandemic.